2010
DOI: 10.1080/09638190903003010
|View full text |Cite
|
Sign up to set email alerts
|

Good or bad? The influence of FDI on productivity growth. An industry-level analysis

Abstract: This paper attempts to reconcile the often inconclusive evidence on the role of FDI in the process of economic development by taking into account the heterogeneity both among industries and among countries. Using a comparable database at the industry level for 35 countries in the OECD, Asia and Eastern Europe from 1987 to 2002, we test for the influence of both stage of development and sectoral FDI patterns in the relationship between FDI and productivity growth. In certain industries and for the catching-up c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 14 publications
1
32
0
6
Order By: Relevance
“…Second, we analyse the different impact of FDI according to sector characteristics and, in particular, to capital intensity and technological level, finding that the effect on growth is much stronger in capital-intensive and in high-tech industries. This is consistent both with the results of Nunnemkamp and Spatz (2004), showing that US FDI stocks have a different impact on the GDP growth of developing economies depending on industry characteristics, and with the more recent analysis of Fillat and Wörz (2011), showing that the potential for FDI flow spillovers differs across sectors and industries. To the best of our knowledge, ours is the first attempt to distinguish the effect of FDI on growth according to the sectors' capital intensity.…”
Section: Introductionsupporting
confidence: 90%
“…Second, we analyse the different impact of FDI according to sector characteristics and, in particular, to capital intensity and technological level, finding that the effect on growth is much stronger in capital-intensive and in high-tech industries. This is consistent both with the results of Nunnemkamp and Spatz (2004), showing that US FDI stocks have a different impact on the GDP growth of developing economies depending on industry characteristics, and with the more recent analysis of Fillat and Wörz (2011), showing that the potential for FDI flow spillovers differs across sectors and industries. To the best of our knowledge, ours is the first attempt to distinguish the effect of FDI on growth according to the sectors' capital intensity.…”
Section: Introductionsupporting
confidence: 90%
“…Moving on to industrial sector, Fillat and Woerz (2011) conducted an empirical analysis for examining the impact of FDI on output and productivity using industrial level data for a panel of 35 OECD, Asian and Eastern European countries. Their study concluded that FDI inflows lead to higher labor productivity and output in industrial sector of ‗catching-up' or developing countries as compared to developed countries but the productivity differs across industries.…”
Section: International Studiesmentioning
confidence: 99%
“…It can also facilitate technology transfer, promote competition in the domestic input market and contribute to the host country's corporate tax revenues. [20][21][22] Governments offer a range of incentives to attract FDI, including tax holidays, land grants and other forms of subsidies, and legal protections beyond those offered to domestic investors.…”
Section: Investor Protection and Public Health Nutrition Policymentioning
confidence: 99%